Status gizi dengan kejadian TB paru balita berdasarkan klasifikasi weight for age (WAZ) - Nur Faridatul Amla; Ema Novita Deniati (Program Studi Ilmu Keperawatan-fakultas Ilmu Kesehatan Universitas Malahayati, 2026)
Background: Tuberculosis (TB) remains a leading cause of death in Indonesia. The provinces with the highest caseloads West Java, East Java, and Central Java account for approximately 47% of all TB cases in the country. TB among children aged 0–14 years ranks second in terms of prevalence. East Java ranks sixth regarding cases of undernutrition and severe malnutrition. Purpose: To determine the association between nutritional status and other risk factors influencing the incidence of pulmonary TB in children under five years of age. Method: This study employed a quantitative approach with an observational, analytical, cross-sectional design. Data were obtained from the 2022 Indonesian Nutritional Status Survey conducted by the Ministry of Health of the Republic of Indonesia. Purposive sampling was used, resulting in a sample of 26,210 children under five. Statistical analysis included univariate analysis, the chi-square test, and multiple logistic regression. Results: Statistically significant associations were found regarding nutritional status (P=0.022; OR=1.57), maternal education (p=0.019; OR=0.29), and pneumonia diagnosis (p=0.000; OR=11.1). Regarding contact history, a